2021
DOI: 10.1002/cssc.202002707
|View full text |Cite
|
Sign up to set email alerts
|

Moisture‐Resistant FAPbI3 Perovskite Solar Cell with 22.25 % Power Conversion Efficiency through Pentafluorobenzyl Phosphonic Acid Passivation

Abstract: Perovskite solar cells (PSCs) have shown great promise for photovoltaic applications, owing to their low‐cost assembly, exceptional performance, and low‐temperature solution processing. However, the advancement of PSCs towards commercialization requires improvements in efficiency and long‐term stability. The surface and grain boundaries of perovskite layer, as well as interfaces, are critical factors in determining the performance of the assembled cells. Defects, which are mainly located at perovskite surfaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(72 citation statements)
references
References 47 publications
1
70
0
1
Order By: Relevance
“…Recently, Akram et al developed a moisture‐resistant PSC structure by passivating the surface of perovskite (FAPbI 3 ) by 2,3,4,5,6‐penta‐fluorobenzyl‐phosphonic acid (PFBPA) and achieved a PCE of 22.25%. [ 53 ] With scanning electron microscopy (SEM) images, the authors showed surface improvements by passivating with PFBPA. The devices were kept in 40−75% RH for 600 h for stability testing.…”
Section: Stability Of the Perovskite Layermentioning
confidence: 99%
“…Recently, Akram et al developed a moisture‐resistant PSC structure by passivating the surface of perovskite (FAPbI 3 ) by 2,3,4,5,6‐penta‐fluorobenzyl‐phosphonic acid (PFBPA) and achieved a PCE of 22.25%. [ 53 ] With scanning electron microscopy (SEM) images, the authors showed surface improvements by passivating with PFBPA. The devices were kept in 40−75% RH for 600 h for stability testing.…”
Section: Stability Of the Perovskite Layermentioning
confidence: 99%
“…[25,26] Apart from defect-related instability issues of PSCs, moisture or oxygen uptake are also considered to be important degradation mechanisms. [27] Owing to its crucial location in a regular n-i-p PSC, the HTL plays a key role in preventing environmental degradation caused by the contact with moisture and/or oxygen. [28] In particular, an intrinsically hydrophobic HTL can partially solve these above-mentioned issues due to the formation of a barrier between the highly hydrophilic ionic perovskite and the surrounding environment.…”
Section: Introductionmentioning
confidence: 99%
“…1 Standard solar spectral [7]. Hybrid organic-inorganic PSCs have had a great interest since 2009 with Power Conversion Efficiency (PCE) which raised exponentially from 3.8% [8] to 6.5% in 2011 [7] to about 23.3 % in 2016 [7] and reaches 25.2 % by 2021 [9][10][11][12][13] as shown in Fig. 2.…”
Section: Introductionmentioning
confidence: 99%